2018
DOI: 10.1002/jcb.27587
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin attenuates myocardial ischemia‐reperfusion injury through Akt/NF‐κB pathway

Abstract: Background: Baicalin can attenuate myocardial ischemia-reperfusion (I/R) on damage. However, the mechanisms are still not fully understood. The study aimed to investigate the antiapoptosis and anti-inflammatory effects of baicalin on myocardial I/R-induced injury. Methods:We established male rats I/R model, and baicalin was intragastric administration after ischemia onset. All experimental animals were randomly divided into five groups: group I, sham; group II, I/R; group III, 50 mg/kg; group IV, 100 mg/kg; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…Our results showed that the levels of P65 phosphorylation were observably down‐regulated at the expression of proteins in neonatal MI model rats after treatment with diosmetin. The research has exhibited 45 that activation of the p13/Akt pathway inhibits MIRI injury, inhibits cardiomyocyte apoptosis and inflammation, but inhibits NF‐κB‐P65 signalling, consistent with our results. Cardiomyocyte apoptosis and inflammation are associated with inhibition of pathway.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that the levels of P65 phosphorylation were observably down‐regulated at the expression of proteins in neonatal MI model rats after treatment with diosmetin. The research has exhibited 45 that activation of the p13/Akt pathway inhibits MIRI injury, inhibits cardiomyocyte apoptosis and inflammation, but inhibits NF‐κB‐P65 signalling, consistent with our results. Cardiomyocyte apoptosis and inflammation are associated with inhibition of pathway.…”
Section: Discussionsupporting
confidence: 92%
“…NF‐κB refers to a number of DNA binding proteins that specifically bind to the κB site of the promoters of various genes and promotes transcription, which plays an important role in cell growth regulation, inflammatory responses, and immune responses . Recently, there has been renewed interest in baicalin suppressed myocardial inflammation and apoptosis via inhibiting NF‐κB pathway . Huang et al hold the view that Arginase‐2 protected rats myocardial I/R injury by suppressing inflammatory response through inhibition of NF‐κB signaling .…”
Section: Discussionmentioning
confidence: 99%
“…28 Recently, there has been renewed interest in baicalin suppressed myocardial inflammation and apoptosis via inhibiting NF-κB pathway. 29 Huang et al hold the view that Arginase-2 protected rats myocardial I/R injury by suppressing inflammatory response through inhibition of NF-κB signaling. 30 There is some evidence to demonstrate that cold inducible RNA-binding protein preserved H9c2 cells from cardiomyocyte via inhibiting NF-κB pathway.…”
Section: Downregulated Expression Of Mir-27 In Myocardial Ischemia mentioning
confidence: 99%
“…Baicalin, a major bioactive component of Scutellaria which is a traditional Chinese medicine herb, has been demonstrated to possess multiple pharmacological activities, such as anti-inflammatory, anti-oxidant, and anti-tumor activities (Luan et al, 2018 ; Sherwani et al, 2018 ). In this study, we confirmed that baicalin has no anti- S. aureus properties but inhibits SrtB activity significantly.…”
Section: Introductionmentioning
confidence: 99%